Mekanisme Impeachment Presiden dalam Sistem Ketatanegaraan Indonesia - I Gede Ngurah Bayu Krisna; Gusti Bagus Suryawan; Wayan Arthanaya (Warmadewa Press, 2020)
In the course of the Indonesian Constitution, the president has been dismissed four times. This is the cause of the dispute between the two state institutions, namely the Representative Council (DPR) and the President. However, after reformation, the process of dismissing the President had to go through several stages. Based on these problems, this study aims to analyze the impeachment mechanism of the President in the Indonesian constitutional system and to find out the consequences of the Constitutional Court's legal decisions upon the DPR's request. This research uses the normative type by looking at the 1945 Constitution of the Republic of Indonesia concerning impeachment. The data sources used were law and documentation. Then, all data is processed and analyzed with deductive-inductive legal arguments. The results showed that before the reformation, government power was very large and centralized, giving birth to an undemocratic government, and the impeachment process of the President used political rather than juridical reasons. However, after the reform era, the regulation was made clear by the changes to the three 1945 Constitution that gave birth to a new institution, namely the Constitutional Court, automatically the post-reform Impeachment must go through a new legal institution after that a political institution